PENGARUH E-COMMERCE, BRAND IMAGE DAN ONLINE CUSTOMER REVIEW TERHADAP MINAT TAMU MENGINAP DI ARTOTEL SANUR BALI - Ida Bagus Ardita Dwipayadnya; I Gusti Ayu Imbayani; I Made Surya Prayoga (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
This study aims to determine the role of e-commerce, brand image and online customer review both jointly and partially as well as knowing the dominant influencing variables on buying interest in consumers of Artotel Sanur Bali. The independent variables used in this study are e-commerce, brand image, online customer reviews. While the dependent variable is buying interest. The research method used in this study is a quantitative research method using a sample determined by non-probability sampling technique with the accidental sampling so that the total sample is 102 people. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that e-commerce, brand image and online customer reviews significant effect on guests' desire to stay at Artotel Sanur Bali. Future research can develop this research by using other variables that theoretically have an influence on buying interest, such as price.